The Effects of Enriched and Typical Laboratory Environments on Object Investigation in Old Sprague Dawley Rats. - Linberts, Andrea June; Linberts, Jessica (My University, 2007)
The purpose of this study was to observe the differences in object investigation between two groups of aged Sprague Dawley rats reared in an enriched and a typical laboratory environment. Research has shown that enrichment has a positive effect on behavior of young and mature rats. Our research question was: Will this positive effect on behavior be retained into old age? Object investigation was measured by recording exploratory activity and overall time spent with objects in an open field. Twelve rats were tested with six in each group. There was no significant difference found in bouts of behavior between the typical and enriched group on Day 1 or Day 2. However, there was a significant difference between the time engaged with objects on Day 1 but not on Day 2. Overall, the results of the study did not support the hypothesis that the enriched group would engage in significantly more object investigation, measured by bouts of behavior and time duration, than the typical laboratory group. Further research on the effects of environment on behavior of the old is important to understand how to maximize functioning through environmental stimulation in old age.
Oshkosh Scholar, Volume 2, 2007, p. 35-42.
Keywords: Rats; Rats - - Behavior